Metastatic squamous cell carcinoma of mediastinal lymph nodes from the ileum: a case report and literature review - Zhang, Yanan; Yue, Yumeng; Zhao, Zongxing; Liu, Haifeng (Frontiers in Oncology, 2025)
Mediastinal lymph node metastasis from squamous cell carcinoma (SCC) is one of the most common sites for regional metastasis in thoracic malignancies. However, SCC originating from the ileum is relatively rare. We herein report a case of mediastinal lymph node metastasis as the first manifestation of postoperative ileal SCC. No primary tumor was detected on comprehensive imaging studies and bronchoscopy in this patient, and endobronchial ultrasound (E-BUS) considered metastatic SCC. After undergoing four cycles of postoperative chemotherapy with the XELOX regimen, the patient experienced rapid disease progression; however, a subsequent change to a treatment regimen of paclitaxel and cisplatin resulted in a favorable response. This article details the patient’s clinical presentation and treatment course and includes a literature review of primary SCCs arising from the jejunum and ileum, thereby enhancing understanding of these uncommon small intestine tumors.